The perception of family physicians on the costs of medicines and diagnostic tests (Portuguese Journal of Family Medicine and General Practice, 2002)
A two-round Delphi procedure was carried out by the authors to collect data on the perceptions of Cascais Health Centre family doctors on the costs ascribed to drug prescription, and ancillary diagnostic and therapeutic means, at their family planning, antenatal, well-child, adult care, urgent care and domicilliary care clinics. The mean percentages obtained in the pannels second round were considered to be the groups consensus results, and they shall be incorporated into the elaboration of Cascais Health Centres annual budget and activity plan.
Keywords: Budget; Activity Plan; Delphi; Drugs; Medicines; Ancillary Diagnostic Means; Ancillary Therapeutic Means